2021
DOI: 10.1097/sla.0000000000004908
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing the Short-term Outcomes of Enhanced Recovery After Surgery and Conventional Care in Laparoscopic Distal Gastrectomy (GISSG1901)

Abstract: Objective: This study aimed to compare the effects of ERAS and conventional programs on short-term outcomes after LDG. Summary of Background Data: Currently, the ERAS program is broadly applied in surgical areas. Although several benefits of LDG with the ERAS program have been covered, high-level evidence is still limited, specifically in advanced gastric cancer. Methods: The present study was designed as a randomized, multicenter, unblinded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…1). [20][21][22][23][24][25][26][27][28][29][30] The quality of the included literature was mainly of low and medium risk, with high reference value (Fig. 2).…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [20][21][22][23][24][25][26][27][28][29][30] The quality of the included literature was mainly of low and medium risk, with high reference value (Fig. 2).…”
Section: Literature Retrieval Resultsmentioning
confidence: 99%
“…Compared with traditional open surgery, laparoscopic surgery itself has the advantages of less trauma and faster postoperative recovery. [42] Besides, this procedure does not require preoperative bowel preparation and allows patients to eat liquid food and glucose to supplement Wang Y 2021 [20] 44 54.5 ± 5.4 25/19 44 55.2 ± 6.0 20/24 (1) (2) (3) (4) Kang SH 2018 [21] 46 56.3 ± 10.4 33/13 51 54.5 ± 12.6 38/13 (1) (3) Weindelmayer J 2021 [22] 248 60-76 154/94 103 60-78 55/48 (3) (4) Jeong O 2021 [23] 219 61.9 ± 11.4 146/73 219 61.2 ± 10.8 145/74 (3) (4) Tian Y 2022 [24] 186 58.3 ± 10.5 129/57 184 58.6 ± 10.9 124/60 (1) (2) (3) (4) (5) Xiao SM 2022 [25] 50 72. (3) (4) (5) Desiderio J 2018 [26] 20 61.0 ± 16.0 8/12 40 63.0 ± 14.0 19/21 (1) (2) (3) (4) Chen JX 2022 [27] 23 67.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from racial and age differences, another reason may be that all patients received standardized perioperative care based on the standardized Enhanced Recovery After Surgery (ERAS) protocol among the three externally verified centres. Over the past two years, ERAS has developed appreciably and has become an important part of the perioperative treatment of gastric cancer [ 40 ]. Our preliminary study showed that implementation of ERAS principles has the potential to reduce surgical stress, reduce the incidence of postoperative adverse events and improve patient long-term prognosis, particularly for elderly patients [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…All enrolled patients adhered to the enhanced recovery after surgery (ERAS) program, which is the routine care mode utilized in our center (19). The ERAS program consists of preoperative pre-rehabilitation therapy, no preoperative mechanical bowel preparation, fasting for 6 hours before surgery, orally glucose infusion until 2 hours before surgery, intraoperative target-oriented liquid management, local anesthesia in the deep incision, general anesthesia combined with epidural anesthesia, early removal of urinary catheter and abdominal drainage tube, early bedside activity, multimodal postoperative analgesia, and sequential enteral nutrition treatment after awakening.…”
Section: Randomization and Interventionmentioning
confidence: 99%